2002
DOI: 10.1159/000049897
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Renal A<sub>1</sub> Adenosine Receptors in vivo

Abstract: We have compared renal A1 adenosine receptor (AR) regulations in rats after chronic agonist and antagonist treatments. In one group, R-phenylisopropyladenosine (R-PIA), a selective A1 AR agonist, was infused subcutaneously for 7 days. Another group was fed theophylline, a non-selective AR antagonist, for 2 weeks. Renal cortex membrane A1 AR binding with 1,3-[3H]-dipropyl-8-cyclopentylxanthine demonstrated ∼40% reduction in the Bmax for the R-PIA group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…It has been reported that in some conditions such as acute renal failure, the expression of A 1 adenosine receptors is increased in the renal cortex while reduced in the IM, which helps to explain the abnormalities in renal function ( Smith et al ., 2000 ). There is no clear explanation for these alterations in receptor expression, but mechanisms such as up and downregulation and G protein coupling may be involved ( Lee et al ., 2002 ). We could speculate that in hypothyroidism, thyroid hormone imbalance may induce changes in adenosine receptor expression in the kidney.…”
Section: Discussionsupporting
confidence: 75%
“…It has been reported that in some conditions such as acute renal failure, the expression of A 1 adenosine receptors is increased in the renal cortex while reduced in the IM, which helps to explain the abnormalities in renal function ( Smith et al ., 2000 ). There is no clear explanation for these alterations in receptor expression, but mechanisms such as up and downregulation and G protein coupling may be involved ( Lee et al ., 2002 ). We could speculate that in hypothyroidism, thyroid hormone imbalance may induce changes in adenosine receptor expression in the kidney.…”
Section: Discussionsupporting
confidence: 75%
“…3,5 Typical of G-protein-coupled receptors, A 1 AR density is subject to up-and downregulation: chronic agonist or antagonist stimulation leads to up or downregulation of A 1 ARs, respectively, in several organs including the kidney. [6][7][8] We have previously demonstrated that chronic treatments with a non-selective AR agonist abolished the protective effects of adenosine in a human proximal tubule cell line (HK-2) against hydrogen peroxide (H 2 O 2 )-mediated injury. 5 Moreover, chronic treatments with a non-selective AR antagonist in HK-2 cells increased the endogenous tolerance to H 2 O 2 .…”
mentioning
confidence: 99%